Educação bilíngue: uma revisão da literatura - Crisp, Alice Battaglia [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
A globalização influencia o cotidiano das pessoas, e uma das muitas consequências, é o desenvolvimento da língua inglesa cada vez mais presente na vida da população. Todos são influenciados por esta. Dessa forma, dominar o inglês é algo necessário, e as crianças não ficam de fora desse contexto. O objetivo central deste trabalho é abordar uma revisão da literatura sobre a educação bilíngue. O trabalho realizará uma revisão de estudos sobre educar uma criança em duas línguas ao mesmo tempo, já que esse é um tema que gera dúvida em muitos pais. Ao mesmo tempo que aprender inglês cedo poderá facilitar o aluno um dia a conquistar vagas de emprego multilíngues, há a dúvida sobre se irá prejudicar seu desenvolvimento e aprendizagem. Propõe-se, apresentar análises e reflexões sobre as vantagens e desvantagens de ensinar precocemente o inglês para uma criança nos tempos atuais. Esse estudo se fundamenta na revisão da literatura, de ordem qualitativa.

Globalization is responsible for the routine of people, and one among the various consequences, is the development of the English language, which is more and more present in our lives. Everybody is affected by it. So, to master the English language is really necessary, and the children are included in this scenario. The main objective of this work is to review the literature about the bilingual education. Teaching a child in a second language (English) on early years would give her / him conflicts? This work will show a review of studies about educating a child in two languages at the same time, because this subject brings a lot of doubts in many parents. Although learning english on early age will help the students to reach vacancies in multilingual jobs, some believe that this may be harmful for his / her development and learning. It will present analysis and reflections about the advantages and disadvantages of teaching English to a child on early age nowadays. This study is based on bibliographic survey in a qualitative way.
Bilingual education: a literature review
Keywords: Educação bilíngue; Bilinguismo; Inglês; Bilingual education; Bilingualism; English